THE SOCIO-PEDAGOGICAL NECESSITY OF MODERNIZING THE SYSTEM OF TRAINING FUTURE PHYSICAL EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
This article analyzes the theoretical-methodological foundations of the development of knowledge about sports aesthetics in future physical education teachers, the practical methodical system of developing knowledge about sports aesthetics, the effectiveness of developing knowledge about sports aesthetics, and its necessity and pedagogical relevance today are covered in detail.